Antioxidant supplementation does not alter endurance training adaptation - Yfanti, C.; Akerström, T.; Nielsen, S.; Nielsen, A. R.; Mounier, R.; Mortensen, O. H.; Lykkesfeldt, J.; Rose, A. J.; Fischer, C. P.; Pedersen, B. K. (Medicine & Science in Sports & Exercise, 2010)
Background: There is a considerable commercial market, especially within the sports community, claiming the need for antioxidant supplementation. One argument for antioxidant supplementation in sports is that physical exercise is associated with increased reactive oxygen and nitrogen species (RONS) production, which may cause cell damage. However, RONS production may also activate redox-sensitive signaling pathways and transcription factors, which subsequently, may promote training adaptation.